Efektivitas Media Komik Digital Interaktif untuk Meningkatkan Kemampuan Menulis Narasi Siswa Sekolah Dasar - Sindhu Setyo Nugroho; Sri Kasih; Nur Puji Hastuti (Universitas Muria Kudus, 2025)
This classroom action research addresses elementary students’ low narrative writing performance, particularly in idea development, text structure, and mechanics. Interactive digital comics were implemented as a visual-textual scaffold to support story planning and narrative construction. The study involved 25 sixth graders at SDN Wangunrejo 01 and was conducted in two cycles (planning, action, observation, reflection). Data were collected through narrative writing tests, classroom observations, brief interviews, and documentation. Quantitative scores were analyzed descriptively, while qualitative process data were examined through triangulation. Results indicate a steady improvement in the mean score from 56.8 (pre-action) to 70.4 (Cycle I) and 82.6 (Cycle II). Students demonstrated better story ideas, more coherent plot organization, improved cohesion, and more accurate spelling and punctuation. Increased motivation, engagement, and willingness to share ideas were also observed. The findings suggest that interactive digital comics effectively function as an idea generator and structural scaffold for narrative writing in primary education.